UJI VALIDITAS E-LKPD BERBASIS KEARIFAN LOKAL PADA MATERI KEANEKARAGAMAN HAYATI UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS - Siti Nurlailliyah (JPB - Jurnal Pendidikan Biologi, 2024)
Student Worksheet (LKPD) is an essential component in the learning process. The use of printed LKPD is currently considered less effective in enhancing students' skills, which affects their learning outcomes. As an alternative, the Electronic Student Worksheet (E-LKPD) based on local wisdom serves as an innovative teaching material that integrates technology with the environment, making it easier for students to understand the material and improve their learning outcomes, particularly in developing critical thinking skills. This study aims to develop a valid E-LKPD based on local wisdom, based on assessments from expert validators in content, language, and media. The research method used is Research and Development (R&D), with the ADDIE development model consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. However, this study focuses only on the Development stage. The validity of the product is measured using a validation instrument evaluated by experts in content, language, and media. Based on the evaluation results, the local wisdom-based E-LKPD scored an average of 84% in the content aspect, 84% in the language aspect, and 84% in the media aspect, all within the valid category. Overall, the E-LKPD obtained an average score of 84% and is declared ready for trial use.